Model for Development of Teaching Materials for Lecture on Tax Accounting with Computer Tax Programs - Jasman Saripuddin Hsb, S.E., M.Si (KUMPULAN JURNAL DOSEN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA)
Model for Development of Teaching Materials for Lecture on Tax Accounting with Computer Tax Programs